Pengenalan Kurikulum Merdeka Belajar Kepada Peserta Didik di SD Mutiara Indah - Rezeki Putra Gulo; Sariani Hia; Erwin Zai (Jurnal Suara Pengabdian 45, 2023)
This PkM activity was held at Mutiara Indah Elementary School, Kualeu Village, Oinlase District, East Tengah Selatan District, So'e City. The method used is a field survey and library research. The PkM activities carried out were an attempt to "introduce the Free Learning Curriculum for Students at Mutiara Indah Elementary School". The background for organizing this activity, namely: Students at Mutiara Indah Elementary School do not yet understand and apply the Merdeka Curriculum in the learning process. This is because some teachers at Mutiara Indah Elementary School still do not understand in depth about this new curriculum, and some teachers even use K-2013. Referring to this problem, the PkM organizing team offered several ideas in the form of activities, namely: Conducting introductory education on the Free Learning Curriculum at Mutiara Indah Elementary School. This activity includes an explanation of the meaning, function, benefits, and how to apply the Independent Curriculum to learning activities in the classroom and outside the classroom.